ANALISIS PENGARUH PENDAPATAN TERHADAP KEPEMILIKAN MOBIL DAN SEPEDA MOTOR PADA RUMAH TAGGA DI SEPANJANG KORIDOR TRAYEK TRANS SARBAGITA - Wirahaji, I B.; Wedagama, D. M. Priyantha; Suthanaya, P. Alit (JURNAL SPEKTRAN; Vol. 2, No.2, Juli 2014, 2014)
Sarbagita region is currently facing problems such as traffic congestion roads. High private vehicle ownership has a direct impact on the community in using public transport. Secondary data are extensively used in this study are from selected households along the corridor in 4 (four) Trans Sarbagita service. The data used is household income, family composition (number of members, workers, and students), ownership of motor vehicles (the number of cars and motorcycles), trip purpose (work, school and shopping). Statistical Package for Social Science (SPSS) version 20 software is used to perform a multinomial logit regression. In addition, GDP and inflation for 5 (five) years in Denpasar and Badung regency which is used to estimate the household income during the next 20 years. Analysis shows that household income <Rp. 3 million have increased the probability of car ownership and car 1 ? 0 motorcycle. In 2017 and 2032, this income affect household vehicle ownership respectively 36.4% and 46.5%. Meanwhile, the influence of household income of Rp. 3-5 million increase for type 0 cars and motorcycles ? 0 and 1 ? 0 cars and motorcycles. In 2017 and 2032, household income affect the ownership of the vehicle amounted to 34.6% and 38.7%. In 2017 and 2032, household income affect the ownership of the vehicle from one car and motorcycle ? 0, respectively by 33.9% and 35.3%.
Keywords: Household Income, Type of Vehicle Ownership, Multinomial Regression Logit